Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 1993
DOI: 10.1115/93-gt-137
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Tip Clearance Control for Centrifugal Compressor of an APU Engine

Abstract: To master todays demand for efficiency and compactness of centrifugal compressor components for small gasturbine engines the main attention must not only be given to the aerodynamic design of the impeller and diffuser components, but also to the installation situation of the surrounding parts. A vital aspect is the tip clearance control between impeller and shroud casing over the total operating range. Using the radial compressor for a small gasturbine engine, developed at BMW Rolls-Royce, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Most of the experimental studies on tip clearance effects in high speed centrifugal compressors therefore consist of measurement of performance characteristics, such as pressure rise across the stage, efficiency and surge margin. Such measurements have been carried out by Mashimo et al (1979), Klassen et al (1977 a and b),Beard et al (1978),Schumann et al (1987),Eisenlohr and Chladek (1994),Palmer and Waterman (1995) andMattern et al (1997). The magnitude of reduction in efficiency of compressors tested in these studies correlated reasonably well with the curves shown inFig.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Most of the experimental studies on tip clearance effects in high speed centrifugal compressors therefore consist of measurement of performance characteristics, such as pressure rise across the stage, efficiency and surge margin. Such measurements have been carried out by Mashimo et al (1979), Klassen et al (1977 a and b),Beard et al (1978),Schumann et al (1987),Eisenlohr and Chladek (1994),Palmer and Waterman (1995) andMattern et al (1997). The magnitude of reduction in efficiency of compressors tested in these studies correlated reasonably well with the curves shown inFig.…”
supporting
confidence: 68%
“…In the case of centrifugal compressors, active control of tip clearance has been found effective (Weimer, 1992). By simply reversing the tilt of the guide vane carrier, Eisenlohr and Chladek (1994) controlled the transient clearance between the impeller and casing to the steady state value during the starting of the compressor. Palmer and Waterman (1995) utilized splitter vanes in the impeller of the first and second stages of a two-stage centrifugal compressor, thereby reducing the vane loading.…”
Section: Methods To Reduce Tip Clearance Effects In Centrifugal Comprmentioning
confidence: 99%
“…Although the focus of this study is on the diffuser design, alternative improvement solutions can be found for example from the tip clearance. Increasing the tip clearance has a negative impact on the stage efficiency and the pressure ratio of the compressor [30,8,31]. Still, the impact of the increasing tip clearance on compressor efficiency can vary according to the compressor characteristics [43].…”
Section: Studied Efficiency Improvement Scenarios For Centrifugal Commentioning
confidence: 96%
“…The influence of the tip clearance flow on the performance and flow structure in centrifugal compressors has been studied by many researchers [4][5][6][7][8][9][10][11][12][13][14]. In previous studies, it was found that the swirling flows and vortex motions within unshrouded impellers are sensitive to the tip clearance flow.…”
Section: Introductionmentioning
confidence: 99%